An Integrated Modelling Approach for the Seismic Collapse Assessment of Masonry Towers. Issue 1 (2nd January 2023) - Mehrotra, Anjali; Liew, Andrew; Block, Philippe; DeJong, Matthew J.
ABSTRACT: Failure of tall slender masonry structures during earthquakes often involves partial collapse of the structure well-above ground level. Consequently, the elastic response of the structure needs to be considered, which often requires modal analysis using finite element models — the generation of which can be labour-intensive and time-consuming. This paper presents a new integrated modelling approach which combines finite element analysis with rocking dynamics to model the seismic response of complex structural geometries in a computationally-efficient manner. The modelling strategy is implemented within the open-source computational framework COMPAS and is incorporated within the broader framework of a tool being developed for the seismic collapse assessment of masonry structures. The framework of this tool is first outlined, and the utility of the new modelling approach then demonstrated through application to the seismic assessment of a three historic masonry towers in North-Eastern Italy. The importance of accounting for elastic amplification effects, as well as the influence of varying boundary conditions on the dynamic response, is also illustrated.